Risks and occupational health in state employment: Analysis of coexisting psychosocial profiles - Marsollier, Roxana Graciela; Expósito, Cristián David (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The objective of this study is to identify the psychosocial profiles of state employees based on the burnout-engagement model and other associated factors. 147 administrative staff of a Government Offices in Mendoza, Argentina participated. Different psychometric tests were applied to measure burnout, engagement, characteristics of the job, psychosocial climate and perception of mobbing. The methodological design is quantitative, descriptive-explanatory. The results obtained allow us to identify the coexistence of different psychosocial profiles in the same labor context, an important input for management decision making with a view to generating preventive and corrective strategies in relation to psychosocial risks at work or motivating occupational health. On the theoretical level, it contributes to the dialectical perspective of integrating positive and negative experiences in one same job dynamic.